Antihemolytic Activities of Green Tea, Safflower, and Mulberry Extracts during Plasmodium berghei Infection in Mice - Audomkasok, Suthin (J Pathog, 2014)
Malaria-associated hemolysis is associated with mortality in adult patients. It has been speculated that oxidative stress and inflammation induced by malaria parasite are involved in its pathophysiology. Hence, we aimed to investigate the antihemolytic effect of green tea, safflower, and mulberry extracts against Plasmodium berghei infection. Aqueous crude extracts of these plants were prepared using hot water method and used for oral treatment in mice. Groups of ICR mice were infected with 6 × 10(6) infected red blood cells of P. berghei ANKA by intraperitoneal injection and given the extracts (500, 1500, and 3000 mg/kg) twice a day for 4 consecutive days. To assess hemolysis, hematocrit levels were then evaluated. Malaria infection resulted in hemolysis. However, antihemolytic effects were observed in infected mice treated with these extracts at dose-dependent manners. In conclusion, aqueous crude extracts of green tea, safflower, and mulberry exerted antihemolysis induced by malaria infection. These plants may work as potential source in the development of variety of herbal formulations for malarial treatment.